Teachers’ Perception on Classroom Action Research as One Of The TPD Strategies - Mariani, Nanik; Arini, Dini Noor; Nasrullah, Nasrullah; Hidayat, Fahmi (English Education: Jurnal Tadris Bahasa Inggris, 2020)
Teacher Professional Development (TPD) is one of the teacher strategies to enhance the teachers’ professionalism. In addition to the values gained through them, enrolling in TPD activities represents the commitment of individuals to raising their awareness of their work, looking deeper into it, and identifying opportunities and possibilities to improve it. CAR is one of many strategies for TPD, but one of the most demanding and, at the same time, one of the most powerful. It is demanding because teachers go through different procedures. This requires knowledge and skills in research. This research is aimed to reveal the teachers perspectives towards the implementation of Classroom Action Research. The subjects of the research are 10 teachers in South Kalimantan, Indonesia and are given the open-ended questionnaires of Classroom Action Research implementation in the classroom. The findings of the research show that Classroom Action Research is believed to improve on the teaching and learning process as it can identify the problems that occurred in the classroom. Most of the teachers are aware of the importance of conducting the classroom action research, and it is one of a way to develop their professional development. Then, it is suggested for English teachers to undergo Classroom Action Research in their classroom to ensure the professional development process.